Effect of anodizing voltage on the photocatalytic activity of films formed by titanium dioxide nanotubes - Serikov, T.M.; Baltabekov, A.S.; Aidarova, D.D; Zhanbirbayeva, P.A.; Kuanyshbekova, A.B (Karagandy University of the name of acad. E.A. Buketov, 2022)
The influence of the anodizing voltage during synthesis on the specific surface area and on the photocatalytic activity of the TiO2 nanotube was studied. Films formed by titanium dioxide nanotubes were obtained on the surface of titanium foil by electrochemical anodizing. It has been found that an increase in the anodizing voltage from 20 V to 60 V leads to an increase in the inner and outer diameters of nanotubes, an increase in the growth rate and the interpore distance of nanotubes. The photocatalytic activity of the samples was evaluated by measuring the magnitude of the photoinduced current. The film produced at low voltage generated a current 3.5 times higher than the film produced at high voltage, and the degradation of the dye in the presence of the films was 75 and 38%, respectively, over the same period of time. An increase in the photocatalytic activity of the films is mainly associated with an increase in the specific surface area of the nanotubes. Thus, the values of the specific surface area of TiO2 nanotubes were determined by the method of lowtemperature nitrogen adsorption. It has been established that with an increase in the anodizing voltage, the specific surface area of the films decreases.
Keywords: nanotube; titanium dioxide; photocatalysis; specific surface area; splitting of water